PEMBENTUKAN KARAKTER PESERTA DIDIK MELALUI KEGIATAN RUTIN SHALAT DHUHA: karakter religius, karakter gotong royong, karakter disiplin dan karakter mandiri - al farobi, afif; Budiman, M. Yusuf (Inisiasi : Jurnal Manajemen Pendidikan Islam, 2023)
Abstract: This study is motivated by the phenomenon of moral degradation that occurs in the younger generation. The role of study is descriptive qualitative and uses data analysis techniques, namely discourse analysis. Data collection techniques use observation and interview techniques. Observations were carried out by coming directly to the study location, interviews were carried out by taking samples of school residents, namely teaching staff, students and education staff. In the study, four character educations were found that resulted from routine Duha prayer activities, namely (1) religious, (2) mutual cooperation, (3) discipline, (4) independence. Keywords: Character Building, Duha Prayer Program.